AN INVESTIGATION OF TEACHER CANDIDATES' METAPHORIC PERCEPTIONS REGARDING THE VIRTUAL CLASSROOM - Göloğlu Demir, Cennet; Çetin, Filiz (International Online Journal of Education and Teaching, 2022)
Determining the metaphorical perceptions of teacher candidates with regard to the concept of virtual classroom is the purpose of this research. 199 prospective teachers studying at Gazi University participated in the study. The opinions of prospective teachers were tried to be presented by means of a qualitative method in this research. The data were obtained from 199 students. By applying the content analysis method, the data were analyzed. A total of 156 metaphors were obtained as a result of the analysis. The relevant codes are gathered together and the metaphors with similar meanings were collected under nine different categories. These categories were determined as waste of time, unfruitful, source of information, comfort, restriction, effectiveness, boring, obligation, and limited communication. As a consequence of the research, it was concluded that more than half (58%) of the metaphors asserted by the teacher candidates about the virtual classroom involved negative (waste of time, unfruitful, restriction, boring, limited communication) judgments, while a third (34%) of the prospective teachers were positive (source of information, comfort, effectiveness). Other teacher candidates (8%) defined the virtual classroom as an obligatory system. Positive and negative metaphors created by prospective teachers didn’t have significant differences in terms of gender and departments.